Electrical discharge machining (EDM): A review - Banu, Asfana; Ali, Mohammad Yeakub (Deer Hill Publications, 2016)
Electro discharge machining (EDM) process is a non-conventional and non-contact machining operation which is used in industry for high precision products. EDM is known for machining hard and brittle conductive materials since it can melt any electrically conductive material regardless of its hardness. The workpiece machined by EDM depends on thermal conductivity, electrical resistivity, and melting points of the materials. The tool and the workpiece are adequately both immersed in a dielectric medium, such as, kerosene, deionised water or any other suitable fluid. This paper provides an important review on different types of EDM operations. A brief discussion is also done on the machining responses and mathematical modelling.